INVESTIGASI PENGARUH MARITAL PARTNERS ROLE PADA HOUSEHOLD CONFLICT IN PURCHASE DECISION OF LOW PRICES FURNITURE STUDI KASUS: KOTA PADANG - Mike Yolanda; Hesti Mariaputri (Ekonis: Jurnal Ekonomi dan Bisnis, 2019)
Families have a big influence on the decision to purchase a product. In a family, often the decision to buy home supplies such as furniture is the decision of one or more family members, especially couples. Husband or wife will give influence in every purchase decision. This study discusses the Investigation of the Effects of Marital Partners on the Household Conflict in Purchase Decision of Furniture Low Prices in the City of Padang. In presenting the research data will use frequency distribution, while the variables used are factors that will influence the couple in making decisions on purchasing low prices furniture. Obtained a relationship between the influence of the couple with the purchase decisions made by consumers in the city of Padang. Keywords: purchasing decisions, consumer behavior in purchasing, family influence on purchases